Association of serum alpha-1 antitrypsin level with the severity of COPD - Dhar, Uma; Rijvy, M. Tanimul Haque; Dip, Abir Hasan; Quadry, Shafiul Azam; Alam, M. Shariful; Hossain, A. K. M. Mosharraf; Islamv, Samprity; Paul, Susanta Kumar; Rahim, Abdur; Chakrabortty, Rajashish (International Journal of Research in Medical Sciences, 2024)
Background: Alpha-1 antitrypsin deficiency (AATD) is a hereditary disorder linked to early onset COPD, notably the emphysema variety, but often goes undetected. Low serum AAT levels may impact lung function and correlate with COPD severity. The aim of the study was to detect possible associations of serum AAT level with the severity of COPD patients on the basis of post bronchodilator FEV1 in Bangabandhu Sheikh Mujib Medical University (BSMMU). Methods: A cross-sectional study was conducted at the Department of Respiratory Medicine, BSMMU, Dhaka, from October 2022 to September 2023. Adult patients (≥18 years) of both genders diagnosed with COPD based on spirometry were included. COPD was defined per GOLD guidelines, with a post-bronchodilator FEV1/FVC ratio <70%. Severity was categorized based on post-bronchodilator FEV1% predicted. Association between serum AAT level and COPD severity was analyzed using SPSS version 26, with significance set at p <0.05. Results: The study involved 80 COPD patients, with 1.25% showing low serum AAT levels and 98.75% normal. No significant differences in age, sex, or smoking status were observed among severity groups. Mean serum AAT levels varied across severity groups but were not statistically significant (p=0.377). Smoking was prevalent (66.3%), with common comorbidities like hypertension (26.3%), IHD (16.3%), and diabetes mellitus (15.0%). Shortness of breath (95.0%) and cough (92.5%) were common symptoms, with most patients having moderate disease severity (42.5%). Conclusions: The study indicates a weak association between serum AAT levels and COPD severity, with only 1.25% of 80 patients exhibiting low AAT levels.